Implementasi Metode Halaqah dalam Program Tahfidz Masjid Al-Ikhwan Tebet Barat Jakarta Selatan di DKI Jakarta - Zihny, Muhammad Haekal; Waluyo, Kasja Eki; Nur, Tajudin (Peneliti.net, 2025)
This study investigates the implementation of the Halaqah Method in the Tahfidz Program at Al-Ikhwan Mosque, Tebet Barat, South Jakarta, using a qualitative research approach. The Halaqah Method, as a group learning approach in the Islamic tradition, was adopted to deepen understanding of the Qur'an and build participants' spiritual character. The research involved an analysis of relevant literature describing how the Halaqah Method is applied in the context of Tahfidz education, its effectiveness in achieving learning objectives, and its impact on participants' spiritual and social development. The findings from this literature study are expected to provide insights into the success of the Halaqah Method in improving the quality of learning in mosques and Islamic educational institutions, particularly in South Jakarta.